Penggalian Potensi Pariwisata Desa Bangelan Sebagai Upaya Peningkatan Perekonomian Di Kecamatan Wonosari ,Kabupaten Malang (Fakultas Teknik, Universitas Brawijaya, 2024)
One of the villages in Wonosari Subdistrict that has a lot of tourism potential is Bangelan Village. This village has an area of 167.20 hectares. Tourism in Bangelan Village utilizes the natural beauty of the village, namely the Tanaka Waterfall tourist attraction located in Arjomulyo Hamlet and jeep tours. This village is the focus of research because of the existence of tourism areas that play an important role in driving the economy of the local community. By using a qualitative descriptive method, it is expected that the tourism potential in Bangelan Village can be explored optimally. This research aims to explore the potential and development opportunities of Bangelan Village, especially in the context of Tourism managed by the Bangelan Village Community. The results showed that Bangelan Village has many tourism potentials that can be developed. Tourism development must be accompanied by good management from the community. Tourism development is expected to encourage the improvement of the community's economy in Bangelan Village.